2019
DOI: 10.1016/j.nicl.2019.101687
|View full text |Cite
|
Sign up to set email alerts
|

Resting state network modularity along the prodromal late onset Alzheimer's disease continuum

Abstract: Alzheimer's disease is considered a disconnection syndrome, motivating the use of brain network measures to detect changes in whole-brain resting state functional connectivity (FC). We investigated changes in FC within and among resting state networks (RSN) across four different stages in the Alzheimer's disease continuum. FC changes were examined in two independent cohorts of individuals (84 and 58 individuals, respectively) each comprising control, subjective cognitive decline, mild cognitive impairment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 77 publications
1
68
0
Order By: Relevance
“…Our findings of destruction in the IFOF, ILF, and SLF in the aMCI and AD groups were consistent with previous ROIbased and voxel-based DTI studies, which showed damage of the WM regions outside the medial temporal lobe (MTL) network in AD patients (34). Our results supported the hypothesis that AD had a disconnection process (38).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of destruction in the IFOF, ILF, and SLF in the aMCI and AD groups were consistent with previous ROIbased and voxel-based DTI studies, which showed damage of the WM regions outside the medial temporal lobe (MTL) network in AD patients (34). Our results supported the hypothesis that AD had a disconnection process (38).…”
Section: Discussionsupporting
confidence: 92%
“…That finding of increased functional connectivity parallels the lack of segregation between the DMN and frontoparietal networks that have been revealed using a graph theory approach in AD, and to a lesser extent, MCI patients [41]. Graph theory investigations of the brain look at the shape of information transfer at a high level, i.e., the network/connectome level.…”
Section: Introductionmentioning
confidence: 57%
“…However, many groups have also observed lower connectivity between these regions in individuals with SCD [18,[76][77][78][79]. Others have reported no difference from control [60], or intricate patterns of greater and lower functional connectivity in individuals with SCD [51][52][53][54][55], suggesting that a complex reorganization of processing responsibilities across network nodes may occur. Multifaceted patterns of increased and decreased connectivity between regions could reflect breakdown in processing within a subnetwork that shifts processing load to more intact components of the broader network.…”
Section: Brain Network Functional Connectivity In Subjective Cognitivmentioning
confidence: 99%